Novel Scalable and Simplified System to Generate Microglia-Containing Cerebral Organoids From Human Induced Pluripotent Stem Cells - Bodnar, Brittany; Zhang, Yongang; Liu, Jinbiao; Lin, Yuan; Wang, Peng; Wei, Zhengyu; Saribas, Sami; Zhu, Yuanjun; Li, Fang; Wang, Xu; Yang, Wenli; Li, Qingsheng; et al. (Frontiers in Cellular Neuroscience, 2021)
Human cerebral organoid (CO) is a three-dimensional (3D) cell culture system that recapitulates the developing human brain. While CO has proved an invaluable tool for studying neurological disorders in a more clinically relevant matter, there have still been several shortcomings including CO variability and reproducibility as well as lack or underrepresentation of certain cell types typically found in the brain. As the technology to generate COs has continued to improve, more efficient and streamlined protocols have addressed some of these issues. Here we present a novel scalable and simplified system to generate microglia-containing CO (MCO). We characterize the cell types and dynamic development of MCOs and validate that these MCOs harbor microglia, astrocytes, neurons, and neural stem/progenitor cells, maturing in a manner that reflects human brain development. We introduce a novel technique for the generation of embryoid bodies directly from inducible pluripotent stem cells (iPSCs) that involve simplified steps of transitioning directly from 3D cultures as well as orbital shaking culture in standard 6-well culture plate. This allows for the generation of MCOs with an easy-to-use system that is affordable and accessible by any general labs.